Diurnal Periodicity of Spore Discharge in Ganoderma boninense Pat. from Oil palm in Malaysia - How, Y. W.; Nawawi, A. (1986)
Spore sampling with a Hirst spore trap in an oil palm area infected with G. boninense 'showed that the concentration of G. boninense spores was low in the day especially from noon to 16.00 hr and was very high at night from 22.00 - 06.00 hr; the peak being around midnight. Sampling with a modified hygrothermograph and a Hirst spore trap of spores discharged from individual sporophores of G. boninense produced from infected oil palm trunks in the Botany Garden of University of Malaya also showed a similar pattern of nocturnal maximum and daytime minimum. SUbjecting sporophores to a constant temperature of between 26 - 28°C and relative humidity of85 - 90% in the laboratory did not result in any apparent changes in the diurnal periodicity of spore discharge.